Gadolinium‐Doped Persistent Nanophosphors as Versatile Tool for Multimodal In Vivo Imaging. (20th November 2014) - Maldiney, Thomas; Doan, Bich‐Thuy; Alloyeau, Damien; Bessodes, Michel; Scherman, Daniel; Richard, Cyrille
<x xml:space="preserve">Abstract</x> Recent breakthroughs in the rational development of multifunctional nanocarriers have highlightened the advantage of combining the complementary forces of several imaging modalities into one single nanotool fully dedicated to the biomedical field and diagnosis applications. A novel multimodal optical‐magnetic resonance imaging nanoprobe is introduced. Designed on the basis of a spinel zinc gallate structure doped with trivalent chromium and gadolinium, this nanocrystal bears the ability to serve as both a highly sensitive persistent luminescence nanoprobe for optical imaging, and a negative contrast agent for highly resolved magnetic resonance imaging (MRI). Additional proof is given that surface coverage can be modified in order to obtain stealth nanoparticles highly suitable for real‐time in vivo application in mice, showing delayed reticulo‐endothelial uptake and longer circulation time after systemic injection.